Sexual function in Brazilian female adolescents and young adults: a cross-sectional study - Negri,Mariana (2022)
SUMMARY OBJECTIVE: The aim of this study was to investigate and compare the sexual function of Brazilian adolescents and young women who were using popular contraceptive methods. METHODS: This cross-sectional study took place in 2012–2014 in a free family planning clinic of a tertiary teaching hospital in Brazil. Participants were female adolescents (10–19 years) and young adults (20–24 years) who were using barrier (condom) or hormonal contraceptive methods. The Female Sexual Function Index questionnaire was used to assess the sexual function in the last 4 weeks. RESULTS: A total of 199 women (128 adolescents and 71 young adults) were included. There were no significant differences in the mean total Female Sexual Function Index scores of adolescents and young adults (26.6±5.7 versus 27.6±6.2, respectively, p=0.264). Compared to young adults, adolescents had significantly lower mean scores for orgasm (3.9±1.5 versus 4.4±1.4, p=0.020) and dyspareunia (4.4±1.6 versus 5.2±1.5, p=0.001; lower scores indicate more dyspareunia). There were no significant differences in the proportion of adolescents versus adults classified as being at risk for sexual dysfunction (38.3 versus 42.3%, p=0.651) or at risk of low desire (18.0 versus 21.1%, p=0.579). CONCLUSION: Nearly 40% of Brazilian female adolescents and young adults are at risk for sexual dysfunctional symptoms and 19% have low desire, without significant differences between the two age groups.